Come out swinging : the changing world of boxing in Gleason's gym - Trimbur, Lucia, 1975- (Princeton University Press, 2013)
Gleason's Gym is the last remaining institution of New York's Golden Age of boxing. Jake LaMotta, Muhammad Ali, Hector Camacho, Mike Tyson--the alumni of Gleason's are a roster of boxing greats. Founded in the Bronx in 1937, Gleason's moved in the mid-1980s to what has since become one of New York's wealthiest residential areas--Brooklyn's DUMBO. Gleason's has also transformed, opening its doors to new members, particularly women and white-collar men. Come Out Swinging is Lucia Trimbur's nuanced insider's account of a place that was once the domain of poor and working-class men of co.